Hedendaagse Sculpturale Keramiek in België. - Stedelijke Kruidtuin, Leuven (Leuven : Stadsbestuur van Leuven, 1983)
Ausloos, Anne ; Cavens, Fri ; De Blok, Luc ; De Bruyn, Anne-France ; Dehert, Wies ; Detige, Christian ; De Vinck, Antoine ; De Vos, Freddy ; De Wolf, Walter ; Goyvaerts, Vic ; Hoys, Marnix ; etc.
Hedendaagse Sculpturale Keramiek in België, Stedelijke Kruidtuin, Leuven, 18 juni - 18 september 1983
boek